EFEKTIFITAS PENERAPAN LARANGAN PEMAKAIAN TELEPON SELULER DI DALAM PESAWAT UDARA BERDASARKAN UNDANG UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN (STUDI KASUS BANDARA SULTAN SYARIF KASIM II PEKANBARU) - Prayoga Darsa; Zulfikar Jayakusuma; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The influence of cellphones on the plane is very large. Cellular phones causeinterference with the aircraft's steering system or the navigation system. Disturbancesoriginating from the cellphone will make the flight direction deviate, the HIS indicator(Horizontal Situation Indicator) is interrupted, VOR (VHF Omnidirecttional Receiver)cause noise is not heard, navigation system interference, communication frequencyinterference, fuel indicator interference and automatic steering system interference. Theinterference caused by the cellphone was not only when the plane was flying, but whenthe plane was moving on the runway, the noise on the heads of the pilots did not receiveinstructions from the watchtower properly.The type of research used in this legal writing is sociological legal research,which is a study of the effectiveness of the law that is in effect or research on legalidentification. Whereas if seen from the nature of this research is descriptive. This studyuses primary data, namely data obtained from the field through interviews andsecondary data, namely data that has been prepared.The results of this study are the effectiveness of the implementation of the ban oncell phone use in aircraft based on Law Number 1 of 2009 concerning Aviation (thecase study of the Sultan Syarif Kasim II airport in Pekanbaru) has not been effectivebecause airlines as less professional operators have implemented prohibitionregulations. cellular telephone in an aircraft. On the other hand the government as theparty that regulates, supervises and enforces regulations is still not optimal in takingaction on conditions that occur in the field and does not have firmness in the regulationof airlines that do not meet safety standards. Legal actions that can be taken on the useof cellular telephones in aircraft based on Law No. 1 of 2009 concerning Aviation (casestudy of the Sultan Syarif Kasim II Pekanbaru airport) subject to criminal sanctions forpassengers who disturb order can be punished with a maximum of 1 (one ) year or amaximum fine of Rp.100,000,000.00 (one hundred million rupiah) in accordance withthe provisions of Article 412 paragraph (2) of Law Number 1 of 2009 concerningAviation. Whereas the use of cellular telephones can be subject to a maximum jailsentence of 2 (two) years or a maximum fine of Rp. 500,000,000.00 (five hundredmillion rupiah) in accordance with the provisions of Article 412 paragraph (1) of LawNumber 1 of 2009 concerning Aviation.Keywords: Effectiveness, Prohibition, Use of Cellular Phones, Aircraft.